Prevalence, symptomatology, pathogenicity and nutritional requirement of Colletotrichum gloeosporioides causing premature fruit drop in Kinnow - and R.C. GARG, ANIL KUMAR*, J. N. SHARMA (Indian Phytopathology, 2012)
Premature fruit drop is the serious diseases of kinnow in Paonta valley of Himachal Pradesh and was found to be prevalent in all kinnow growing areas under survey with maximum of 45.50 per cent incidence and 70.90 per cent disease severity at Ranput village of Sirmour district in Paonta valley. Colletotrichum gloeosporioides was identified to be associated with disease. The typical symptoms of the disease were observed on the stalk end of kinnow fruit. The pathogenicity test was conducted by artificial inoculation of young kinnow fruit at stalk-end with the test fungus and typical symptoms were produced after twelve days of inoculation. Amongst different solid and liquid media tested, potato dextrose, Richardâ€™s and sucrose medium supported maximum growth and sporulation of the causal Â fungus. Fungus could grow at a temperature ranging from 5-350C with an optimum at 250C. Vegetative growth and sporulation was maximum at pH 5.0 and 6.0, respectively. The pathogenic fungi grew and sporulated maximum when basal medium was supplemented with maltose and fructose as carbon source and showed maximum vegetative growth and sporulation with ammonium sulphate and sodium nitrate as nitrogen source.